The German organ transplant scandal: the collective mindsets of physicians - Pohlmann, Markus; Höly, Kristina (Organizational crime, 2023)
On the backdrop of the “German Organ Transplant Scandal”, we explore the question of which unwritten rules were supportive of guideline violations within transplant centers. This contribution follows on from the previous contribution “The German Organ Transplant Scandal: An Analysis of Court Records and Official Documents from the Medical Association” by complementing it in the question of the causes of organizational deviance in transplant medicine. We examine the extent to which competitive pressure, hierarchical context, justification, and internalization as four typical mechanisms from organizational sociology and criminology are responsible for the emergence and spread of deviance. On the basis of a collective mindset analysis (CMA) of a total of 62 interviews with physicians and medical staff as well as a participant observation in a transplant center, we conclude that guideline violations are a special form of organizational deviance, namely professional deviance, which focused on the realization of a professional claim to sovereignty.
Gesehen am 12.05.2023